Are Physical Libraries Popular for Research in the Internet Age Post COVID-19?. Issue 4 (2nd October 2022) - Adetayo, Adebowale Jeremy
Abstract: The study investigates if physical libraries are popular for research by students in the internet age post COVID-19. The study used a descriptive survey research design. The population consisted of 3457 Adeleke University undergraduates. Descriptive statistic was used to analyze data. The findings suggested that physical libraries are increasingly less popular among students for research purposes, owing mostly to the development of the internet era. Other reasons cited include physical library congestion and excessive surveillance, a preference to read with friends outside of the physical library, and a lack of motivation to visit the physical library. It was also discovered that students have a culture of completing their own research rather than paying professionals to do it for them. The study concluded that physical libraries are less popular for research among students, majorly due to the popularity of the internet. As a result, the study recommends that library management make physical libraries the strongest internet hub on campus, where all students would want to come for research. More efforts should be made to expand physical libraries and provide a variety of quiet reading options for those who detest crowds.